Polypropylene film for new energy automobile capacitor and preparation method thereof
By using titanium salt and polyester materials to prepare the impregnation liquid and ultraviolet irradiation, a dense titanium dioxide layer is formed, which solves the problem of insufficient bonding strength between the polypropylene film and the metal plating layer, and improves the performance and stability of the film capacitor.
Patent Information
- Application Number
- CN202411606110.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The bonding strength between the polypropylene film and the metal coating is insufficient, which affects the performance of the film capacitor.
The impregnation liquid is prepared using raw materials such as titanium salt, terephthalic acid, isophthalic acid and ethylene glycol, and the polypropylene film is soaked in the liquid, hydrochloric acid is added dropwise and ultraviolet irradiated to form a dense titanium dioxide precursor layer , improve the surfactivity of the polypropylene film and the interfacial bonding ability with the metal coating.
The interface bonding strength between the polypropylene film and the metal coating is significantly improved, the breakdown strength and stability of the film capacitor are enhanced, and the damage to the material structure of the modification treatment in the prior art is avoided.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitor manufacturing, and in particular to a polypropylene film for new energy vehicle capacitors and a preparation method thereof. Background Art
[0002] The electronic control system of new energy vehicles requires a stable voltage to ensure normal operation, especially during rapid acceleration and deceleration. Capacitors can provide additional current in an instant to achieve voltage stabilization and ensure the normal operation of the electronic control system. In addition, capacitors can store electricity at high voltage and release electricity at low voltage, thereby improving the energy efficiency of new energy vehicles. Therefore, the performance of capacitors has a vital impact on new energy vehicles.
[0003] Polypropylene film is a common substrate for film capacitors, which has the advantages of low specific gravity, stable chemical properties, low cost, and mature technology. One of the shortcomings of polypropylene film as a substrate for film capacitors is that the bonding strength between it and the metal coating still has room for improvement. Summary of the invention
[0004] One of the problems solved by the present invention is how to provide a polypropylene film that can be closely combined with a metal coating.
[0005] In order to solve at least one of the above problems, the present invention provides a method for preparing a polypropylene film for a capacitor of a new energy vehicle, the preparation method comprising: S100, preparing a base film using raw materials including polypropylene resin; S200, preparing an impregnation solution using raw materials including titanium salt, terephthalic acid, isophthalic acid, and ethylene glycol; S300, immersing the base film in an impregnation liquid, adding hydrochloric acid to the impregnation liquid and irradiating it with ultraviolet light to obtain a modified polypropylene film.
[0006] In the above technical solution, the raw materials for preparing the base film also include 1,4-benzenedicarboxaldehyde, 4,4'-diaminobiphenyl and N-hydroxynaphthaleneimide trifluoromethanesulfonic acid.
[0007] In the above technical solution, the raw materials for preparing the base film also include ethylene-1-octene copolymer and polyethylene.
[0008] In the above technical solution, S200 specifically includes: S210, feeding glycerol, terephthalic acid, isophthalic acid and ethylene glycol into an esterification reaction kettle at a mass ratio of glycerol: terephthalic acid: isophthalic acid: ethylene glycol = (5-10): (80-120): (80-120): 100, stirring and reacting at a temperature of 230° C. to 240° C. until the esterification rate reaches 95%, and then discharging the material to obtain an esterification product; S220, according to the mass ratio of catalyst: stabilizer: modifier: ethylene glycol = (0.1-0.2): (0.1-0.2): (25-30): 100, according to the amount of ethylene glycol added in S210, weigh the catalyst, stabilizer and modifier, and send them into the polycondensation reaction kettle together with the esterification product, and react under reduced pressure at a temperature of 240° C. to 260° C. for 2 h to 4 h to obtain a polycondensation product; S230, uniformly mixing the dispersant, silane coupling agent, titanium salt, polycondensation product and N,N-dimethylformamide in water according to the mass ratio of dispersant: silane coupling agent: titanium salt: polycondensation product: N,N-dimethylformamide: water = (0.2-0.4): (0.4-0.6): (15-20): (20-25): (20-25): 100 to obtain a premixed solution; S240, heat the premixed liquid to 60° C. to 70° C., add ethanol in an amount 2 to 2.5 times the mass of the titanium salt dropwise under heat preservation conditions and stir simultaneously, and continue to heat preservation and stirring for 1 to 1.5 hours after the addition is completed to obtain an impregnation solution.
[0009] In the above technical scheme, the catalyst includes antimony acetate, the stabilizer includes trimethyl phosphate, the modifier includes 5-(sodium sulfonate)isotitanate liquid, the silane coupling agent includes γ-aminopropyltriethoxysilane, the dispersant includes sodium hexametaphosphate, and the titanium salt includes tetrabutyl titanate.
[0010] In the above technical solution, S300 specifically includes: S310, injecting the impregnation liquid into the treatment tank and heating it to 50° C. to 60° C., and then immersing the base film in the impregnation liquid; S320, adding a hydrochloric acid aqueous solution to the impregnation liquid, and simultaneously applying ultraviolet radiation to the basement membrane in the impregnation liquid; S330, stopping the dripping after the pH value of the impregnation solution reaches 3 to 4, and continuing to apply ultraviolet radiation for 2 to 3 hours; S340, after the ultraviolet irradiation is completed, the base film is taken out, washed and dried at normal pressure at a temperature of 110° C. to 115° C. to obtain a modified polypropylene film.
[0011] In the above technical solution, during the process of dripping the hydrochloric acid aqueous solution and applying ultraviolet radiation, oxygen is introduced from the bottom and / or the side of the treatment tank for bubbling.
[0012] In the above technical solution, the concentration of the hydrochloric acid aqueous solution is 36% to 38%, and the power of the ultraviolet irradiation is 400W to 600W.
[0013] In the above technical solution, the thickness of the polypropylene film is 5 μm to 20 μm.
[0014] The present invention also provides a polypropylene film for new energy vehicle capacitors, and the polypropylene film is obtained by using the preparation method of any of the above technical solutions.
[0015] Beneficial Effects The preparation method of the present invention first adopts raw materials including polypropylene resin to prepare a base film; then adopts raw materials including titanium salt, terephthalic acid, isophthalic acid, and ethylene glycol to prepare an impregnation liquid; finally, the base film is immersed in the impregnation liquid, hydrochloric acid is added to the impregnation liquid, and ultraviolet irradiation is performed to obtain a modified polypropylene film.
[0016] Using terephthalic acid, isophthalic acid and ethylene glycol as raw materials, a polyester material with more polar groups can be prepared through esterification and polycondensation reactions. By mixing the polyester material and titanium salt, an impregnation solution containing free titanium ions can be prepared. After the base film is immersed in the impregnation solution, hydrochloric acid is added dropwise to adjust the pH value, and the titanium salt can be solified under the action of an acidic catalyst, and deposited on the surface of the base film to form a uniformly distributed dense titanium dioxide precursor.
[0017] Ultraviolet irradiation can generate free radicals from titanium dioxide, and promote the polar groups in polyester to combine with the free radicals of titanium dioxide precursors to form interaction points and chemical bonds. As a result, the surface free energy of the polypropylene base film can be increased and its wetting properties can be improved. The titanium dioxide deposition layer formed on the surface of the polypropylene base film can improve the interface bonding ability between the polypropylene substrate and the metal coating, and as an insulating barrier, it can limit charge migration and improve the breakdown strength of the film capacitor. DETAILED DESCRIPTION
[0018] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below in conjunction with specific embodiments of the present invention.
[0019] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0020] The present invention provides a method for preparing a polypropylene film for a new energy vehicle capacitor, the preparation method comprising: S100, preparing a base film using raw materials including polypropylene resin; S200, preparing an impregnation solution using raw materials including titanium salt, terephthalic acid, isophthalic acid, and ethylene glycol; S300, immersing the base film in an impregnation liquid, adding hydrochloric acid to the impregnation liquid and irradiating it with ultraviolet light to obtain a modified polypropylene film.
[0021] Preferably, the polypropylene film has a thickness of 5 μm to 20 μm.
[0022] The purpose of the present invention is to improve a polypropylene film with a stronger interface bonding ability with a metal coating. Polypropylene film is a widely used base film material. By evaporating a conductive metal on the surface of the polypropylene film, a film capacitor product can be prepared. In new energy vehicles, a variety of components including electromagnetic interference capacitors, buffer capacitors, resonant capacitors, power factor correction capacitors, etc. require the use of film capacitors. The physical and chemical properties of the polypropylene base film have a crucial impact on the quality of film capacitor products and the safety performance of new energy vehicles.
[0023] One of the shortcomings of polypropylene film materials when used as base films is that the bonding strength between the polypropylene base film and the metal coating is poor. The reason for the above shortcomings is that polypropylene is a non-polar polymer material with low surface energy, so it is not easy to form a good chemical bond with polar materials such as metals.
[0024] The prior art generally adopts the method of surface modification treatment of polypropylene film materials to solve the above technical problems. For example, the polypropylene film is immersed in a potassium permanganate strong oxidant solution, or the polypropylene film is subjected to corona treatment, or the surface of the polypropylene film is bombarded with high-energy electrons or ions. In addition, an inorganic non-metallic oxide film layer can be formed on the surface of polypropylene by chemical deposition or reaction. Inorganic non-metallic oxides can change the microscopic morphology and roughness of the polypropylene surface, thereby improving the interface bonding strength between polypropylene and the metal coating.
[0025] In general, the above treatment methods have very limited activation degree on the surface of polypropylene film, and the strong oxidant treatment method is easy to destroy the structure of polypropylene, reducing its mechanical properties and aging resistance. For inorganic non-metallic oxide film layer, since it is difficult to control its uniform density with the existing technology, it is easy to have the problem of uneven thickness of inorganic non-metallic oxide film layer, which will affect the evaporation effect of metal coating.
[0026] In view of the above reasons, the present invention is dedicated to providing a method for surface treatment of polypropylene film, so as to improve the interface bonding strength between the polypropylene film and the metal coating when the polypropylene film is used as a base film.
[0027] The method for achieving the above-mentioned purpose of the present invention is to prepare an impregnation solution containing titanium salt and polyester, and when the base film is immersed in the impregnation solution, an acid catalyst is applied to the base film, and ultraviolet irradiation is performed. The basic principle is as follows: the titanium salt can be hydrolyzed and generated under the action of an acid catalyst after being dissolved in a water-alcohol solution, and further polycondensed to form the properties of a nano-scale titanium oxide precursor with a three-dimensional network structure, so that the titanium oxide precursor is deposited on the surface of the base film; terephthalic acid, isophthalic acid and ethylene glycol are used as raw materials, and a polyester material with more polar groups can be prepared through esterification and polycondensation reactions. The polyester has more polar groups, and the polar functional groups contained in it can form interaction points and chemical bonds with the titanium dioxide precursor under ultraviolet light irradiation, thereby improving the surface activity of the polypropylene base film, thereby increasing the chemical bonding points between it and the metal coating, improving the interface bonding ability between it and the metal coating, and thereby improving the breakdown strength of the polypropylene metallized film.
[0028] In some implementations of the present invention, S200 specifically includes: S210, feeding glycerol, terephthalic acid, isophthalic acid and ethylene glycol into an esterification reaction kettle at a mass ratio of glycerol: terephthalic acid: isophthalic acid: ethylene glycol = (5-10): (80-120): (80-120): 100, stirring and reacting at a temperature of 230° C. to 240° C. until the esterification rate reaches 95%, and then discharging the material to obtain an esterification product; S220, according to the mass ratio of catalyst: stabilizer: modifier: ethylene glycol = (0.1-0.2): (0.1-0.2): (25-30): 100, according to the amount of ethylene glycol added in S210, weigh the catalyst, stabilizer and modifier, and send them into the polycondensation reaction kettle together with the esterification product, and react under reduced pressure at a temperature of 240° C. to 260° C. for 2 h to 4 h to obtain a polycondensation product; S230, uniformly mixing the dispersant, silane coupling agent, titanium salt, polycondensation product and N,N-dimethylformamide in water according to the mass ratio of dispersant: silane coupling agent: titanium salt: polycondensation product: N,N-dimethylformamide: water = (0.2-0.4): (0.4-0.6): (15-20): (20-25): (20-25): 100 to obtain a premixed solution; S240, heat the premixed liquid to 60° C. to 70° C., add ethanol in an amount 2 to 2.5 times the mass of the titanium salt dropwise under heat preservation conditions and stir simultaneously, and continue to heat preservation and stirring for 1 to 1.5 hours after the addition is completed to obtain an impregnation solution.
[0029] The catalyst includes antimony acetate, the stabilizer includes trimethyl phosphate, the modifier includes 5-(sodium sulfonate)isotitanate liquid, the silane coupling agent includes γ-aminopropyltriethoxysilane, the dispersant includes sodium hexametaphosphate, and the titanium salt includes tetrabutyl titanate.
[0030] In the above steps, polyester can be obtained by esterification and polycondensation between terephthalic acid, isophthalic acid and ethylene glycol. Esterification is a reaction between alcohol and carboxylic acid to generate ester and water. In this process, the carboxyl group of the carboxylic acid combines with the hydroxyl group of the alcohol to form an ester bond and release water molecules. Specifically, terephthalic acid reacts with ethylene glycol to generate ethylene terephthalate, and isophthalic acid reacts with ethylene glycol to generate ethylene isophthalate. On the basis of the esterification reaction, the generated ester compounds further undergo polycondensation. In this process, multiple ester molecules are interconnected by ester bonds to form a high molecular polyester chain. At the same time, it is accompanied by the removal of water molecules. The polycondensation reaction requires the addition of an appropriate catalyst to promote the reaction.
[0031] Preferably, the present invention uses 5-(sodium sulfonated)isotitanic acid and ethylene glycol to mix and prepare an esterification liquid, and uses 5-(sodium sulfonated)isotitanic acid esterification liquid as a hydrophilic modifier. Wherein, the 5-(sodium sulfonated)isotitanic acid esterification liquid is prepared in the following manner: 5-(sodium sulfonated)isotitanic acid:ethylene glycol = (30-50):100 mass ratio, 5-(sodium sulfonated)isotitanic acid and ethylene glycol are mixed in a reaction kettle and heated to remove water, then the temperature is raised to 180°C to 185°C for esterification reaction, and the reaction is stopped after the esterification rate reaches 80%, to obtain 5-(sodium sulfonated)isotitanic acid esterification liquid.
[0032] In order to prepare a water-soluble polyester with uniform texture and capable of being stably dispersed in a water-alcohol solution, the present invention adds 5-(sodium sulfonate)isotitanic acid ester liquid as a modifier in S220 to improve the hydrophilicity of the polyester. The molecular structure of 5-(sodium sulfonate)isotitanic acid contains a sodium sulfonate group, and the presence of this hydrophilic group makes the compound have good water solubility. When it is introduced into the polyester molecular chain in the polycondensation reaction, it can increase the interaction force between the polyester molecular chain and the water molecules, thereby improving the hydrophilicity of the polyester and obtaining a water-soluble polyester capable of being stably dispersed in a water-alcohol solution.
[0033] In some implementations of the present invention, S300 specifically includes: S310, injecting the impregnation liquid into the treatment tank and heating it to 50° C. to 60° C., and then immersing the base film in the impregnation liquid; S320, adding a hydrochloric acid aqueous solution to the impregnation liquid, and simultaneously applying ultraviolet radiation to the basement membrane in the impregnation liquid; S330, stopping the dripping after the pH value of the impregnation solution reaches 3 to 4, and continuing to apply ultraviolet radiation for 2 to 3 hours; S340, after the ultraviolet irradiation is completed, the base film is taken out, washed and dried at normal pressure at a temperature of 110° C. to 115° C. to obtain a modified polypropylene film.
[0034] Among them, the concentration of the hydrochloric acid aqueous solution is 36% to 38%, and the power of ultraviolet irradiation is 400W to 600W.
[0035] By heating, the reaction activity between the impregnation liquid and the surface of the base film can be increased. As mentioned above, after the base film is immersed in the impregnation liquid, the hydrochloric acid causes the titanium salt to be sol-formed to form a titanium dioxide precursor deposited on the surface of the base film, and the ultraviolet radiation causes the polar groups in the polyester to combine with the free radicals of the titanium dioxide precursor. Preferably, during the process of dripping the hydrochloric acid aqueous solution and applying ultraviolet radiation, oxygen is introduced from the bottom and / or side of the treatment tank for bubbling. Oxygen bubbling can further promote the combination of free radicals and polar groups, increase the reaction activity, and promote the deposition of the titanium dioxide precursor on the surface of the base film.
[0036] Compared to the method of coating a polyester coating containing titanium dioxide on a base film and then irradiating it with ultraviolet light, the present invention adopts a method of preparing an impregnation solution of a mixture of water-based polyester and titanium salt, and immersing and irradiating the base film. This method can avoid the problem of uneven activation modification caused by uneven coating of the polyester coating and poor wettability of the polypropylene base film. In addition, compared to the technical solution of mixing titanium dioxide and polyester to prepare a modified component, the present invention mixes polyester with titanium salt, and when the base film is immersed, the titanium salt is catalyzed by an acidic catalyst to form a titanium dioxide precursor, thereby ensuring that the titanium dioxide precursor is uniformly deposited on the surface of the polypropylene base film.
[0037] The present invention uses relatively low-power ultraviolet rays for relatively long-term irradiation, thereby promoting uniform deposition of the titanium dioxide precursor and effective combination of free radicals and polar groups therein, thereby further ensuring the modification effect on the polypropylene-based film. Compared with the strong oxidant treatment solution, the impregnation solution of the present invention does not damage the polypropylene-based film, which is conducive to maintaining a relatively long service life of the polypropylene-based film under high temperature conditions.
[0038] Polypropylene-based films usually use polypropylene resin as the main material, and may also add auxiliary materials such as polyacrylamide polymers, polypropyleneimine polymers, polyethylene polymers, polystyrene polymers, and additives such as plasticizers, stabilizers, flame retardants, coupling agents, inorganic fillers, etc., and are prepared by melt mixing, sheet casting and biaxial stretching.
[0039] In the above prior art for preparing polypropylene-based films, the problem is that powdered nanoscale inorganic fillers are usually difficult to disperse evenly in polymers and are easily agglomerated, thereby affecting the physical and chemical properties and service life of polypropylene-based films. To solve this problem, in some embodiments of the present invention, 1,4-benzenedicarboxaldehyde, 4,4'-diaminobiphenyl and N-hydroxynaphthaleneimide trifluoromethanesulfonic acid can be added to the raw materials for preparing the base film.
[0040] Specifically, S100 includes the following steps: S110, preparing zirconium oxide using raw materials including 1,4-benzenedicarboxaldehyde and zirconium tetrachloride; S120, preparing a polypropylene resin using raw materials including 4,4'-diaminobiphenyl and polypropylene; S130, melt-mixing, casting and biaxially stretching raw materials including N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, zirconium oxide and polypropylene resin to obtain a base film.
[0041] In the above steps, 1,4-benzenedicarboxaldehyde is added during the preparation of zirconium oxide, and 4,4'-diaminobiphenyl is added during the preparation of polypropylene resin, and then zirconium oxide and polypropylene resin are melt-kneaded together with N-hydroxynaphthaleneimide trifluoromethanesulfonic acid.
[0042] N-hydroxynaphthaleneimide trifluoromethanesulfonic acid is used as a photoacid catalyst. Under subsequent ultraviolet irradiation, the sulfonate bond will break and generate acid and free radicals. The acid and free radicals can catalyze and promote the aldehyde-ammonia condensation reaction between 1,4-benzenedialde supported on zirconium oxide and 4,4'-diaminobiphenyl in polypropylene resin, so that the zirconium oxide dispersed in the polypropylene resin can be organically linked to the imide structure formed by the aldehyde-ammonia condensation reaction between polypropylene. The imide structure can not only improve the heat resistance of polypropylene, but also make zirconium oxide and polypropylene tightly bonded through chemical bonds, promote the uniform and stable dispersion of zirconium oxide in polypropylene, and avoid its agglomeration.
[0043] Preferably, the raw materials for preparing the base film further include ethylene-1-octene copolymer and polyethylene. Further preferably, the weight average molecular weight of polyethylene is 200,000 to 300,000, and the weight average molecular weight of polypropylene is 200,000 to 250,000.
[0044] Considering that the thermal stability of 1,4-benzenedicarboxaldehyde and N-hydroxynaphthalimide trifluoromethanesulfonic acid is not high, in order to avoid the decomposition of the two during the melt mixing process, the present invention adds ethylene-1-octene copolymer and polyethylene to polypropylene, thereby reducing the melt mixing temperature and protecting 1,4-benzenedicarboxaldehyde and N-hydroxynaphthalimide trifluoromethanesulfonic acid. Polyethylene has excellent low temperature resistance and chemical stability, and its melting temperature is relatively low. The introduction of ethylene-1-octene copolymer in polypropylene can interrupt the regularity of polypropylene molecular chains, thereby reducing its crystallinity and melting point. This random copolymerization destroys the ordered structure of the molecular chain, weakens the interaction force between small molecules, increases the distance between molecules, and thus reduces the melting temperature of the material. Therefore, the above steps reduce the melt mixing temperature of polypropylene by adding ethylene-1-octene copolymer and polyethylene, and achieve the effect of protecting 1,4-benzenedicarboxaldehyde and N-hydroxynaphthalimide trifluoromethanesulfonic acid. In addition, selecting polyethylene and polypropylene with lower molecular weight also helps to further reduce the melting temperature.
[0045] Exemplarily, S100 includes the following steps: S111, dissolving 1,4-benzenedicaldehyde in ethanol at a mass ratio of 1,4-benzenedicaldehyde: zirconium tetrachloride: water: ethanol = (2-6): (30-35): (40-45): 100, and then adding zirconium tetrachloride and water and mixing them evenly to obtain a first mixture; S112, adjusting the pH value of the first mixture to 4 to 5 by dropwise adding 36% hydrochloric acid aqueous solution and stirring, and continuing stirring for 2 h to 2.5 h to obtain a zirconium sol; S113, placing the zirconium sol in anhydrous ethanol, and soaking it at a temperature of 40° C. to 50° C. for 18 to 24 hours to obtain a zirconium gel; S114, drying the zirconium gel at a temperature of 100° C. to 120° C. under normal pressure, and grinding the zirconium gel into powder to obtain zirconium oxide; S211, weighing and mixing 4,4'-diaminobiphenyl, ethylene-1-octene copolymer, polyethylene and polypropylene in a mass ratio of 4,4'-diaminobiphenyl:ethylene-1-octene copolymer:polyethylene:polypropylene=(2-6):(4-8):(10-20):100 to obtain a second mixture; S212, sending the second mixture into an internal mixer, mixing at a temperature of 150° C. to 160° C. for 20 min to 40 min, discharging, cooling, and pelletizing to obtain a polypropylene resin; S311, weighing and mixing polyvinyl alcohol, silane coupling agent, N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, zirconium oxide and polypropylene resin according to a mass ratio of polyvinyl alcohol: silane coupling agent: N-hydroxynaphthaleneimide trifluoromethanesulfonic acid: zirconium oxide: polypropylene resin = (1-2): (2-4): (2-4): (4-6): 100 to obtain a third mixture; S312, feeding the third mixture into a twin-screw extruder, and extruding the mixture after melt-mixing at a temperature of 170° C. to 190° C. to obtain a sheet-like fluid; S313, casting the sheet-like fluid through a chilled roller at 80° C. to 100° C. and a high-pressure air knife to obtain a membrane; S314. Stretching the film in the longitudinal direction at a stretching ratio of 4 to 5 times and in the transverse direction at a stretching ratio of 5 to 6 times on a mechanical stretching machine at a temperature of 115 to 125°C, and heat-setting it at a temperature of 150 to 160°C to obtain a base film.
[0046] The purpose of the above steps is to achieve a thorough mixing of 1,4-benzenedicarboxaldehyde and zirconium oxide. 1,4-benzenedicarboxaldehyde is soluble in ethanol. Zirconium tetrachloride, as a zirconium source, can be hydrolyzed in a mixture of water and alcohol with hydrochloric acid as a catalyst to form a zirconium sol mixed with 1,4-benzenedicarboxaldehyde. The zirconium sol can form a zirconium gel after being soaked and aged in anhydrous ethanol. By drying the zirconium gel, zirconium oxide loaded with 1,4-benzenedicarboxaldehyde can be obtained.
[0047] It can be understood that the above steps prepare zirconium oxide powder loaded with 1,4-benzenedicaldehyde by the sol-gel method through the addition conditions of the raw materials. In the prior art, various methods such as supercritical drying and calcination can be used to achieve the conversion of gel into oxide powder. However, considering that supercritical drying will extract 1,4-benzenedicaldehyde and high-temperature calcination will cause thermal decomposition of 1,4-benzenedicaldehyde, the present invention adopts atmospheric pressure drying to prepare zirconium oxide. Among them, the temperature of atmospheric pressure drying is preferably 100°C to 120°C.
[0048] Compared with the method of directly mechanically mixing 1,4-benzenedicaldehyde and zirconium oxide, adding 1,4-benzenedicaldehyde during the preparation of zirconium oxide by the sol-gel method can obtain zirconium oxide uniformly loaded with 1,4-benzenedicaldehyde. The above method helps zirconium oxide to be tightly linked with polypropylene through aldehyde-ammonia condensation.
[0049] In the above steps, the silane coupling agent is preferably γ-aminopropyltriethoxysilane. It is understood that the twin-screw extruder has multiple heating zones, preferably 3 to 4. The temperature of each heating zone can be the same or there can be a gradient change. In general, the temperature range of melt mixing can be controlled at 170°C to 190°C.
[0050] The chilling roller can achieve rapid cooling of the melt sheet fluid through the convection of the heat dissipating liquid in its internal flow channel. The high-pressure air knife can use the high-pressure airflow to blow away the dust and impurities on the surface of the polymer, and accelerate the heat dissipation of the polymer through the high-pressure airflow, so as to obtain a cooled film. The film can be stretched into a polypropylene base film by biaxial stretching in the longitudinal and transverse directions.
[0051] Embodiment 1 In this example, a series of zirconium oxide samples were prepared. The raw material ratios and process parameters are shown in Table 1. The specific process is as follows: S1. According to the raw materials and mass ratios in Table 1, 1,4-benzenedicarboxaldehyde is first dissolved in ethanol, and then zirconium tetrachloride and water are added and ultrasonically mixed to obtain a first mixture. The pH value of the first mixture is adjusted to 4 by dropping a 36% hydrochloric acid aqueous solution and stirring. The stirring is continued for 2 hours to obtain a zirconium sol. S2. The zirconium sol is immersed in anhydrous ethanol to obtain a zirconium gel. The zirconium gel is dried at normal pressure and air-milled into a powder with a particle size of 5 nm to 20 nm to obtain zirconium oxide samples 1 to 2.
[0052] Table 1 Embodiment 2 In this example, a series of polypropylene base film samples for film capacitors were prepared. The raw material ratios and process parameters are shown in Table 2. The specific process is as follows: S1. Weigh and mix the raw materials and mass ratios in Table 2 to obtain a second mixture, send the second mixture into an internal mixer and mix at 155° C. for 30 min, discharge, cool to room temperature, and cut into particles of 0.5 mm to 0.6 mm to obtain a polypropylene resin; S2. Weigh and mix the raw materials and mass ratios in Table 2 to obtain a third mixture, feed the third mixture into a twin-screw extruder for melt mixing and extrusion to obtain a flake fluid, and cast the flake fluid through a 90°C chilled roller and a 90°C high-pressure air knife to obtain a membrane; S3. Stretch the membrane longitudinally at a stretching ratio of 4 times on a mechanical stretching machine, with a preheating temperature of 115°C to 120°C and a stretching temperature of 120°C to 125°C, then stretch it transversely at a stretching ratio of 6 times, with a preheating temperature of 115°C to 120°C and a stretching temperature of 120°C to 125°C, and finally heat-set at a temperature of 150°C to 160°C to obtain base film samples 1 to 4.
[0053] Table 2 Embodiment 3 In this example, a series of polypropylene modified base film samples were prepared. The raw material ratios and process parameters are shown in Table 3. The specific process is as follows: S1. According to the mass ratio of 5-(sodium sulfonated)isotitanic acid:ethylene glycol = 35:100, 5-(sodium sulfonated)isotitanic acid and ethylene glycol are mixed in a reaction kettle and heated to remove water, and then the temperature is raised to 185° C. for esterification reaction. The reaction is stopped after the esterification rate reaches 80%, and 5-(sodium sulfonated)isotitanic acid esterified liquid as a modifier is obtained; S2. According to the raw materials and mass ratios in Table 3, glycerol, terephthalic acid, isophthalic acid and ethylene glycol were fed into an esterification reactor, and the reaction was stirred at a temperature of 240° C. until the esterification rate reached 95%, and then the material was discharged to obtain an esterification product; S3, according to the raw materials and mass ratio in Table 3, according to the amount of ethylene glycol added in the previous step, weigh antimony acetate, trimethyl phosphate and the modifier obtained in S1, and send them into the polycondensation reactor together with the esterification product, first stir and react at normal pressure for 20 minutes under 245°C temperature conditions, then reduce the pressure to 50KPa to 60KPa and stir and react for 60 minutes, and finally reduce the pressure to below 1KPa and stir and react for 60 minutes. After the reaction is completed, introduce nitrogen to return to normal, stop the reaction, and obtain a polycondensation product; S4. According to the raw materials and mass ratios in Table 3, sodium hexametaphosphate, γ-aminopropyltriethoxysilane, tetrabutyl titanate (not included in modified base film sample 5), polycondensation product (not included in modified base film sample 6) and N,N-dimethylformamide were mixed in water to obtain a premixed solution. The premixed solution was heated to 65°C, and ethanol with a mass of 2.5 times the mass of the titanium salt was added dropwise under heat preservation conditions and stirred simultaneously. After the addition was completed, the heat preservation and stirring were continued for 1.5 hours to obtain an impregnation solution. S5. The impregnation solution was injected into the treatment tank and heated to 60°C. Then, the base film sample was placed in the treatment tank. Immerse in the impregnation liquid, introduce oxygen at a rate of 0.1L / min from the bottom of the treatment tank for bubbling, add 36% hydrochloric acid aqueous solution to the impregnation liquid, and simultaneously apply ultraviolet radiation to the basement membrane in the impregnation liquid with a 500W ultraviolet lamp. Stop dripping after the pH value of the impregnation liquid reaches 4, and continue to apply ultraviolet radiation for 3 hours. After the ultraviolet irradiation is over, take out the basement membrane, wash it once with ethanol, wash it twice with water, and dry it at normal pressure at a temperature of 110°C to 115°C for 1 hour to obtain modified basement membrane samples 1 to 6.
[0054] Table 3 Performance parameters Table 4 lists the performance parameters of modified base film samples 1 to 6 prepared in the embodiments of the present invention. Among them, the conditions of the accelerated aging test are placed under an environmental condition of a temperature of 90°C and a relative humidity of 90% for 10 days. After the surface of the modified base film samples 1 to 6 is evaporated with a metal aluminum layer, the breakdown strength thereof as a metallized film is tested. The conditions of vacuum evaporation include: the vacuum degree does not exceed 2×10-5Pa, the evaporation rate is 0.08A / s, the evaporation time is 200s, the substrate temperature is 140°C, the wire feeding speed is 800mm / min, and the evaporation boat temperature is 660°C.
[0055] According to Table 4, modified base film samples 1 and 2 have good heat resistance and breakdown strength. The aging resistance of modified base film sample 2 is relatively good, and it shows more stable performance after the accelerated aging test. The heat resistance of modified base film sample 3 is poor, especially the heat resistance after the accelerated aging test has declined significantly. This result shows that excessively high melt mixing temperature may cause thermal decomposition of raw materials such as 1,4-benzenedialdehyde and N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, hindering the occurrence of aldehyde-ammonia condensation reaction. The breakdown strength of modified base film sample 4 is good, but the heat resistance is not ideal. The heat resistance and aging resistance of modified base film samples 5 and 6 are acceptable, but the breakdown strength is low.
[0056] Table 4 Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a polypropylene film for a new energy vehicle capacitor, characterized in that: The preparation method comprises: S100, preparing a base film using raw materials including polypropylene resin; S200, preparing an impregnation solution using raw materials including titanium salt, terephthalic acid, isophthalic acid, and ethylene glycol; S300, immersing the base film in the impregnation liquid, adding hydrochloric acid to the impregnation liquid and irradiating with ultraviolet light to obtain the modified polypropylene film.
2. The preparation method according to claim 1, characterized in that: The raw materials for preparing the base film further include 1,4-benzenedicarboxaldehyde, 4,4'-diaminobiphenyl and N-hydroxynaphthaleneimide trifluoromethanesulfonic acid.
3. The preparation method according to claim 2, characterized in that: The raw materials for preparing the base film further include ethylene-1-octene copolymer and polyethylene.
4. The preparation method according to any one of claims 1 to 3, characterized in that S200 specifically includes: S210, feeding the glycerol, the terephthalic acid, the isophthalic acid and the ethylene glycol into an esterification reaction kettle at a mass ratio of glycerol: terephthalic acid: isophthalic acid: ethylene glycol = (5-10): (80-120): (80-120): 100, stirring and reacting at a temperature of 230° C. to 240° C. until the esterification rate reaches 95%, and then discharging to obtain an esterification product; S220, according to the mass ratio of catalyst: stabilizer: modifier: ethylene glycol = (0.1-0.2): (0.1-0.2): (25-30): 100, according to the amount of ethylene glycol added in S210, weigh the catalyst, stabilizer and modifier, and send them into a polycondensation reaction kettle together with the esterification product, and react under reduced pressure at a temperature of 240° C. to 260° C. for 2 h to 4 h to obtain a polycondensation product; S230, uniformly mixing the dispersant, the silane coupling agent, the titanium salt, the polycondensation product and the N,N-dimethylformamide in the water according to a mass ratio of dispersant: silane coupling agent: titanium salt: polycondensation product: N,N-dimethylformamide: water = (0.2-0.4): (0.4-0.6): (15-20): (20-25): (20-25): 100 to obtain a premixed solution; S240, heating the premixed liquid to 60° C. to 70° C., adding ethanol in an amount 2 to 2.5 times the mass of the titanium salt dropwise under heat preservation conditions and stirring simultaneously, and continuing to heat preservation and stirring for 1 to 1.5 hours after the addition is completed to obtain the impregnation solution.
5. The preparation method according to claim 4, characterized in that: The catalyst includes antimony acetate, the stabilizer includes trimethyl phosphate, the modifier includes 5-(sodium sulfonate)isotitanate liquid, the silane coupling agent includes γ-aminopropyltriethoxysilane, the dispersant includes sodium hexametaphosphate, and the titanium salt includes tetrabutyl titanate.
6. The preparation method according to claim 4, characterized in that: S300 specifically includes: S310, injecting the impregnation liquid into a treatment tank and heating it to 50° C. to 60° C., and then immersing the base film in the impregnation liquid; S320, adding a hydrochloric acid aqueous solution to the immersion liquid, and simultaneously applying the ultraviolet radiation to the base film in the immersion liquid; S330, stopping the dripping after the pH value of the impregnation solution reaches 3 to 4, and continuing to apply the ultraviolet radiation for 2 to 3 hours; S340, after the ultraviolet irradiation is completed, taking out the base film, washing it and drying it at normal pressure at a temperature of 110° C. to 115° C. to obtain the modified polypropylene film.
7. The preparation method according to claim 6, characterized in that: During the process of dripping the aqueous hydrochloric acid solution and applying the ultraviolet radiation, oxygen is introduced from the bottom and / or the side of the treatment tank for bubbling.
8. The preparation method according to claim 6, characterized in that: The concentration of the hydrochloric acid aqueous solution is 36% to 38%, and the power of the ultraviolet irradiation is 400W to 600W.
9. The preparation method according to any one of claims 1 to 3, characterized in that: The polypropylene film has a thickness of 5 μm to 20 μm.
10. A polypropylene film for capacitors of new energy vehicles, characterized in that: The polypropylene film is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Ultrathin high-temperature-resistant polypropylene capacitor film and manufacturing method thereof
CN115322478A
Anti-ultraviolet PET (Polyethylene Terephthalate) film for photovoltaic back plate and preparation method of anti-ultraviolet PET film
CN115418084A
Anti-ultraviolet card protecting film and preparation process thereof
CN118027834A
Base film for high-temperature-resistant and aging-resistant composite current collector and preparation method of base film
CN118240250A
Copper-zinc polypropylene film, preparation method and application
CN118667211A
Cited By
Metallized film for capacitor and preparation method
CN120600526A
